The Righteousness of Joseph Interpreting Matt 1.18–25 in Light of Judean Legal Papyri - Esler, Philip Francis 1952- (2022)
This article seeks to explain Matthew's description of Joseph as righteous (δίκαιος) by investigating Matt 1.18-25 within its ancient context, especially Judean practices of marriage and divorce as illuminated by Judean legal papyri from the Dead Sea region in the first and second centuries ce and from the Judean politeuma of Herakleopolis in the mid-second century bce. The examination will demonstrate the importance of these papyri for understanding the narrative in Matt 1.18-25 in its original social setting where honour was a dominant value, especially the extent to which it reveals Joseph to be an exemplar of Matthean righteousness.
Keywords: Joseph; Divorce; Exemplar; legal papyri; Marriage; Righteousness